The Effect of Physical Activity Intervention on the Well-Being of Pregnant Women: Literature Review - Tetti Solehati; Afni Faddilah Taslam; Nezla Puspita; Ima Rismawati; Dinyatul Arba Ramdhona; Khalishah Salsabila; Lu'lu Nadiyya Samdjaya; Yuliana Sri Rahayu; Cecep Eli Kosasih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Physical activity during pregnancy needs to be considered because it will have a positive impact in reducing medical interventions during childbirth, such as: amniocentesis, labor induction, and the risk of cesarean section. Low physical activity in pregnant women causes adverse effects, such as: excess weight during pregnancy, diabetes, and hypertension. This study aimed to identify physical exercise that is effective in improving the welfare of pregnant women. Literature review research design. Literature search assisted by Pubmed, Science Direct, and Ebsco databases using the keywords